Identifikasi Faktor yang Mempengaruhi Produktivitas Kerja Pegawai Work From Anywhere (WFA) Menggunakan Metode Systematic Literature Review (SLR) - Neyla Nuril Fauziyah; Diah Priharsari; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The emergence of a work system that has become a new culture in Indonesia or commonly known as Work From Anywhere (WFA). The problem with this study is that from several research journals related to the identification of WFA work productivity factors, there are still many scattered in various journal databases. So it is necessary to unify from various journals about the product factor of WFA work using the SLR method. The first search is to identify based on keywords, year of publication and quality of the journal. Then continued the selection based on the field of discussion and language; abstract and content. From the selection results, a number of 11 factors that affect the productivity of WFA employees were obtained.